Factors Affecting the Achievement of Applying Good Governance Principle in Management of the Bureau of Weights and Measures, Department of Internal Tread, Ministry of Commerce - สุทธนารักษ์ จรินทร; Yimwilai, Chaiya (Sripatum Review of Humanities and Social Sciences, 2021)
The purposes of this research were (1) to study the level of achievement in applying good governance principle in administration, (2) to analyze the factors affecting the achievement of the application of good governance principle in administration, (3) to study problems and obstacles in applying good governance principle in administration, and (4) to propose the guidelines for promoting the application of good governance principle for achievement in administration of the Bureau of Weights and Measures, Department of Internal Trade, Ministry of Commerce. This research was a mixed-method research involving the quantitative and qualitative research methodologies. In the quantitative study, the research sample consisted of 200 personnel of work units under the Bureau of Weights and Measures. The employed research tool was a questionnaire. Data were analyzed using the percentage, mean, and standard deviation. In the qualitative study, the key research informants were 8 administrators of work units under the Bureau of Weights and Measures. The employed research tool was a structured interview form. Data were analyzed with content analysis. Research findings showed that the principle of decentralization had the highest influence on the achievement in applying good governance principle in administration. The achievement in applying good governance principle in administration was at the high level in all aspects, with the aspect of energy saving of the work units receiving the highest rating mean. The problems and obstacles in applying good governance in administration were the following: the lack of personnel with knowledge and expertise; the lack of new technology application in administration; the lack of public relations for operations; the lack of monitoring of progress in operations; and the lack of decentralization. The practical guidelines for promotion of the application of good governance principle in administration were the following: the clients should be allowed to participate in monitoring of progress and evaluation of the operations; the work units should be decentralized by transferring some functions to be undertaken by the private sector to lessen the workload; and the personnel should be developed to equip them with knowledge and expertise to enable them to work more efficiently.